Inhibition of M/Kv7 Currents Contributes to Chloroquine-Induced Itch in Mice - Zhang, Dong; Men, Hongchao; Zhang, Ludi; Gao, Xiangxin; Wang, Jingjing; Li, Leying; Zhu, Qiaoying; Zhang, Hailin; Jia, Zhanfeng (Frontiers in Molecular Neuroscience, 2020)
M/Kv7 potassium channels play a key role in regulation of neuronal excitability. Modulation of neuronal excitability of primary sensory neurons determines the itch sensation induced by variety of itch-causing substances including Chloroquine (CQ). In the present study, we demonstrate that suppression of M/Kv7 channel activity contributes to generation of itch in mice. CQ enhances excitability of the primary sensory neurons through inhibiting M/Kv7 potassium currents in a Ca2+ influx-dependent manner. Specific M/Kv7 channel opener Retigabine (RTG) or Tannic acid (TA) not only reverses the CQ-induced enhancement of neuronal excitability but also suppresses the CQ-induced itch behavior. Systemic application of RTG or TA also significantly inhibits the itch behavior induced by variety of pruritogens. Taken together, our findings provide novel insight into the molecular basis of CQ-induced itch sensation in mammals that can be applied to the development of strategies to mitigate itch behavior.